The ERK1/2 MAPK cascade - Cobb, Melanie H. (Henry Stewart Talks, 2014)
MAPK cascade paradigm, Properties of the MAPK cascade, ERK1/2 in disease and development, Activation of the MAPK cascade, Structure and motifs in the cascade, Generating specificity in MAPK cascades, Docking mechanisms, MAPK scaffolds, Feedback mechanisms and pathway interactions, Regulation of the localization of ERK1/2, MAPKs and transcription